Design of a conformal end-fire array antenna - Wang, Xin Xin (2015)
Substrate-integrated-waveguide (SIW) technology provides us a lot of advantages and flexibilities for integrating planar waveguides with other electromagnetic (EM) structures. Horn antenna is one of the most commonly used antennas. This project aims how to combine SIW with horn antenna concept to design wideband and low-profile conformal antenna. Based on the understanding of previous design methodology for a wideband and low-profile H-plane ridged SIW horn antenna, we further explore the possibility of advanced low-profile horn antenna designs to provide better performance of larger bandwidth, lower VSWR, and better radiation pattern. A modified structure of low-profile ridged SIW horn antenna is proposed to achieve the design goals. The newly proposed ridged SIW horn antenna consists of four layers: (i) ellipse-shaped copper taper with stepped ridge connecting to feed line; (ii) the first substrate layer of Duriod RT 5580 with permittivity of 2.2 and thickness of 0.508 mm; (iii) the second substrate layer of Teflon with permittivity of 2.1 and thickness of 5 mm; (iv) rectangular ground plane. The geometrical parameters of the proposed structure are finalized through EM simulation tool ANSYS. The finalized design model has been fabricated and measured to validate the proposed design structure. It is concluded that (i) the measured results agree well with the simulated results; (ii) the VSWR of the design ridged SIW H-plane antenna is below 2 from 4.2 GHz to 18 GHz; (iii) the designed antenna has very good gain and radiation performance; (iv) it is low-profile with great potential for real applications.